A Low-Cost Solution-Processed PTB7-Based MSM Visible Photodetector - Rana J.S.; Jit S. (My University, 2025)
A low-cost solution-processed poly[[4,8-bis [(2-ethylhexyl)oxy]benzo[1,2-b:4,5-b']dithiophene-2,6-diyl] [3-fluoro-2-[(2-ethylhexyl)carbonyl]thieno[3,4-b]thiophened iyl]] (PTB7)-based metal-semiconductor-metal (MSM) visible-range photodetector is proposed in this article. The PTB7 film is deposited by the sol-gel method on a SiO2 layer obtained by dry oxidation of a Si substrate. To fabricate the required Al/PTB7/Al MSM device structure, Al-based Schottky contacts were thermally deposited over the PTB7 film. The surface morphology obtained by atomic force microscopy (AFM) shows a uniform growth of the polymer film with an average roughness of 0.440 ± 0.146 nm. The UV-visible measurement shows main absorption of the PTB7 film in the visible region with an extension to the near-infrared region (NIR). The proposed device exhibits a maximum responsivity, external quantum efficiency (EQE), and detectivity of 52.5 A/W, 9789%, and sim 1.28times 10^{{13}} Jones, respectively, at 665-nm visible light of intensity sim 1.039~mu text{W} /cm2 at a bias of-3 V. The response time (or rise time) and recovery time (or fall time) of the fabricated photodetector are obtained as 32 and 24 ms at 665 nm, respectively. © 1963-2012 IEEE.